2024
DOI: 10.3847/1538-3881/ad0f93
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Formation of β Pic b through the Composition of Its Parent Protoplanetary Disk as Revealed by the β Pic Moving Group Member HD 181327

Henrique Reggiani,
Jhon Yana Galarza,
Kevin C. Schlaufman
et al.

Abstract: It has been suggested that β Pic b has a supersolar metallicity and subsolar C/O ratio. Assuming solar carbon and oxygen abundances for the star β Pic and therefore the planet’s parent protoplanetary disk, β Pic b’s C/O ratio suggests that it formed via core accretion between its parent protoplanetary disk’s H2O and CO2 ice lines. However, β Pic b’s high metallicity is difficult to reconcile with its mass M p = 11.7 M Jup. Massive stars can present peculiar photospheric ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 130 publications
(136 reference statements)
0
3
0
Order By: Relevance
“…The C/O ratio of HD 181327 was used as a proxy for β Pic since they likely formed out of the same molecular cloud. The C/O ratio of HD 181327 is 0.62 ± 0.08 (Reggiani et al 2024). The C/O ratio for β Pic b we got from the ATMO grid fitting is substellar and does not contain the stellar C/O in its uncertainty.…”
Section: β Pictoris B's Atmosphere Compositionmentioning
confidence: 93%
See 1 more Smart Citation
“…The C/O ratio of HD 181327 was used as a proxy for β Pic since they likely formed out of the same molecular cloud. The C/O ratio of HD 181327 is 0.62 ± 0.08 (Reggiani et al 2024). The C/O ratio for β Pic b we got from the ATMO grid fitting is substellar and does not contain the stellar C/O in its uncertainty.…”
Section: β Pictoris B's Atmosphere Compositionmentioning
confidence: 93%
“…From our modeling with the ATMO grid of all the spectra and photometry in Figure 14 Using the C/O ratio of a planetary atmosphere to infer its formation history requires knowledge of the C/O ratio of the host star; however, there is not a published value for the C/O ratio of β Pic in the literature. Because of this, we compared to the C/O ratio measured from the β Pic moving group member HD 181327 as in Reggiani et al (2024). The C/O ratio of HD 181327 was used as a proxy for β Pic since they likely formed out of the same molecular cloud.…”
Section: β Pictoris B's Atmosphere Compositionmentioning
confidence: 99%
“…With the help of atmospheric forward models and spectral retrievals, they were able to derive a subsolar C/O ratio of ∼0.43 for the atmosphere of β Pic b, suggesting strong volatile enrichment during its formation process if the host star β Pic is assumed to be of similar composition as the Sun. We note that measuring the C/O abundance ratio for β Pic is difficult, but it can be done for other stars in the β Pic moving group, which can serve as a proxy for the chemical composition of β Pic (e.g., Reggiani et al 2024). While the C/O abundance ratio of the host star β Pic can hence be expected to be ∼solar or supersolar, the subsolar C/O ratio of β Pic b has recently been challenged by Kiefer et al (2024), who found that with a more careful treatment of telluric and stellar features, the SINFONI spectrum of β Pic b also supports a ∼solar C/O ratio for the planet.…”
Section: Introductionmentioning
confidence: 99%